2018
DOI: 10.1016/j.bmcl.2018.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Novel polyamine-based Histone deacetylases-Lysine demethylase 1 dual binding inhibitors

Abstract: Epigenetic modulators Histone deacetylases (HDACs) and Lysine demethylase (LSD1) are validated targets for anticancer therapy. Both HDAC1/2 and LSD1 are found in association with the repressor protein CoREST in a transcriptional co-repressor complex, which is responsible for gene silencing. Combined modulation of both targets results in a synergistic antiproliferative activity. In the present investigation, we report about the design and synthesis of a series of polyamine-based HDACs-LSD1 dual binding inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Notably, due to the functional interplay of LSD1 and HDAC1/2 in the CoREST complex, it has been suggested that combined targeting of HDACs and LSD1 might be superior with respect to cancer-specific cytotoxicity compared to individual inhibition of histone acetylation or methylation [39]. Indeed, synergistic effects of combined LSD1/HDAC inhibition could be demonstrated, and several single drugs inhibiting HDACs as well as LSD1 have been developed [3942]. One such compound which has been reported to target class I HDACs as well as LSD1 is domatinostat (4SC-202) [43], which is currently investigated in a phase I clinical trial in hematological neoplasms with up to now excellent tolerability and good efficacy [44].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, due to the functional interplay of LSD1 and HDAC1/2 in the CoREST complex, it has been suggested that combined targeting of HDACs and LSD1 might be superior with respect to cancer-specific cytotoxicity compared to individual inhibition of histone acetylation or methylation [39]. Indeed, synergistic effects of combined LSD1/HDAC inhibition could be demonstrated, and several single drugs inhibiting HDACs as well as LSD1 have been developed [3942]. One such compound which has been reported to target class I HDACs as well as LSD1 is domatinostat (4SC-202) [43], which is currently investigated in a phase I clinical trial in hematological neoplasms with up to now excellent tolerability and good efficacy [44].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, targeting LSD1‐containing complexes by one molecule, such as pan‐KDM inhibitors, and dual LSD1‐HDAC inhibitors has been shown to be effective for targeting cancers and other diseases, because they are expected to show synergistic or additive pharmacological activities. In addition, the strategy of using PDCs ( 21 ) to target cancers overexpressing LSD1 can be applied to other drugs such as cytotoxic drugs and other epigenetic drugs targeting nuclear complexes including LSD1 …”
Section: Discussionmentioning
confidence: 99%
“…Milelli et al developed a series of polyamine‐based hybrid compounds, from which emerged 115 (Figure ), showing interesting inhibitory activity against LSD1 (IC 50 LSD1‐CoREST3 = 3.8 μM) and HDAC1 (Ki HDAC1‐CoREST3 = 42.5 nM) in vitro as well as in cellular assays. In 115 , the two anti‐HDAC and ‐LSD1 pharmacophoric portions were connected using a polyamine‐type chain, since the polyamine moiety can interact with both LSD1 and HDAC enzymes due to protonated nitrogen atoms allowing electrostatic interactions with negatively charge amino acid residues .…”
Section: The Mtdl Approachmentioning
confidence: 99%
“…Among the different polyamine linkers used, the spermine (3‐4‐3), typical of 115 , produced the best enzymatic results. When tested against MCF7 breast cancer cell line, 115 resulted more effective (at high concentration) than vorinostat 3 in inducing cytotoxicity (68.6% vs 56.6% of dead cells) …”
Section: The Mtdl Approachmentioning
confidence: 99%
See 1 more Smart Citation